The impact of partisan politics on service delivery in Zimbabwe’s local authorities : the case of Kadoma city council.2000-2015 - Mleya, Majory (Midlands State University, 2020)
Partisan politics has become an obstacle to countries in Africa and the rest of the world. Zimbabwe, like other African countries, has implemented reforms to decentralize political authority to local government and introduce multiparty elections. This however creates opportunities for partisanship struggles to emerge in local authorities and influence service delivery. In this document it was found that partisan politics undermines service delivery in Kadoma in several ways. Many local authorities have failed to provide basic services to its residents. It is hard for local authorities to point fingers to the partisanship because the issue is very sensitive. Kadoma City Council has failed to deliver quality services to its residents and partisan politics is to blame. Resources that are meant for the smooth running of the council are being used to satisfy private needs. This research therefore aimed at examining the impact of partisan politics on service delivery in local authorities using Kadoma City Council as a case study. Overally, tackling the issue of partisan politics does not only improve service delivery but also promote cooperation, transparency and accountability in the local authorities. The researcher was driven to carry out this research because of the gap that exists in the presented literature about partisan politics and service delivery. There are some challenges that the council face in delivering services in the existence of partisan politics, they include lack of funding, too much central government interventions in local issues, recentralization through forcing local government officers to report to governors, provincial administrators and district administrators, violence during local election, abuses of political power by minister of local government who willingly or constantly has dismissed councilors and mayors.